Fate and Freedom in Ancient Stoicism and Augustine’s Critique - Rosario Neuman Lorenzini; Sergi Grau Guijarro; Miguel Ángel Belmonte (Religions, 2025)
This article is divided into three parts. First, a brief exposition of the ontological foundations of ancient determinism is provided to explain the worldview held by such a philosophical position. The second part sets out the argument used by Chrysippus to make causal determinism compatible with moral responsibility, and points out the tensions that such a position entails. In the third part, the notion of freedom of ancient Stoicism is contrasted with the philosophy of Augustine in order to determine the novelty that Christianity represented in this matter.